Trends in Total Hip Arthroplasty Length of Stay and Coding Status From 2018 to 2021: Two-Year Impact of the Removal From the Inpatient-Only List - Joshua G. Sanchez, BA; Meera M. Dhodapkar, MD; Scott J. Halperin, MD; Will M. Jiang, BS; Jonathan N. Grauer, MD; Lee E. Rubin, MD (Arthroplasty Today)
Background: Total hip arthroplasty (THA) was removed from the Centers for Medicare and Medicaid Services inpatient-only (IPO) list on January 1, 2020. The impact of this policy changes on length of stay (LOS) and coding status (inpatient/outpatient) beyond 2020 remains to be fully defined. Methods: Data were obtained from the 2018 to 2021 National Surgical Quality Improvement Program database. Elective primary THA patients aged 18 y or older were identified by Current Procedural Terminology code. Year of surgery, age (dichotomized at ≥/<65 y old), American Society of Anesthesiologists classification, smoking status, coding status, and LOS were assessed. Pearson chi-squared tests compared categorical variables, while analysis of variance tests evaluated continuous variables. Results: Overall, 156,212 THA patients were identified. Over the 4 y of study, outpatient cases increased by 1392% from 3.7%-5.75% to 35.6%-54.2% (P < .0001). Analogously, average LOS decreased from 1.91-1.75 to 1.50-1.35 d (P < .0001). This pattern of decreased LOS was seen in patients aged ≥65 y (traditional Medicare eligibility, P < .0001) and those <65. Conclusions: These data demonstrate a continued increase in outpatient THA since the IPO list removal, with over half of cases classified as outpatient in 2021 and a corresponding reduction in LOS. Notably, the outpatient status is an administrative designation that was not defined by same-day discharge or lack of overnight stay. The observed changes in both age groups (≥65 and <65 y) underscore the extensive impact of the IPO list removal on surgical practices.